A comparative study of CO2 utilization in methanol synthesis with various syngas production technologies. (December 2015) - Luu, Minh Tri; Milani, Dia; Bahadori, Alireza; Abbas, Ali
Abstract: This paper explores a possible 'methanol economy' transition strategy—a novel carbon capture and utilization (CCU) configuration for methanol (MeOH) production (CCU–MeOH). In this CCU–MeOH, the captured CO2 is co-fed with natural gas (NG) to produce syngas suitable for MeOH synthesis. The main objective of this work is to compare two aspects, namely CO2 emission intensity and the extent of methane reliance, of six CCU–MeOH scenarios derived from four reforming methodologies (steam methane reforming (SMR), dry methane reforming (DMR), bireforming and trireforming). Among the studied CCU–MeOH scenarios, Scenario 2 (DMR with H2 addition) significantly outperformed the other scenarios by 12.7% and 22% on average in terms of CO2 emission intensity and methane reliance, respectively. The outperformance of Scenario 2 in CO2 emission intensity is found to originate from a 22% reduction in CH4 consumption on average compared to the other scenarios. In intermediate term, Scenario 2 may provide an attractive option for transitioning into 'methanol economy' of the future.